Better Opportunities for All : Vietnam Poverty and Shared Prosperity Update - World Bank (World Bank, Hanoi, 2020)
A massive reorganization of the rural labor market is underway, with workers leaving agriculture in large numbers. The agriculture sector has been consistently losing an average of 4 percent of its workforce annually since 2013. Most of those leaving agriculture have remained in rural areas and been absorbed into non-agriculture sectors, which have been creating rural nonagricultural jobs at a rapid pace. Nearly 4 million off-farm jobs have been created in rural areas since 2013, mostly in the industry sector, led by manufacturing. There are now almost as many non-agricultural jobs as agricultural jobs in rural areas. The share of people in wage employment in rural areas has risen dramatically, reaching 38 percent in the first quarter of 2018, compared with just 28 percent in 2013. Unlike densely populated areas, growth of non-agriculture sectors in more distant, low-density areas is normally based on absolute advantage, driven by external demand, and delivered mostly by small and medium enterprises (SMEs) due to the limited scope for achieving scale. Strategies to expand economic opportunities in these areas should aim to: (i) create a secondary economy supporting industries based on the regional absolute advantages; (ii) integrate these areas into the network economy to expand their market potential; and (iii) reduce the cost of migration to increase long-distance migration domestically. This report is therefore focused on identifying the challenges preventing, and ways to enhance, the poor’s participation in more productive income-generating opportunities. The analysis focuses exclusively on rural areas, where 95 percent of the current poor reside. It is presented in four sections. The first section presents the evolution of rural incomes in Vietnam since 2010, showing how non-agricultural incomes have grown in importance and broadly transformed rural livelihoods. The second section then explores the role of household and farm-specific attributes, alongside local economies, in facilitating non-agricultural employment, to identify the most critical factors holding back the poor from being integrated into off-farm activities. The third section turns to opportunities in agriculture. This focuses on identifying challenges and policy remedies for optimizing crop and land-use choices among lagging groups to maximize their agricultural incomes. The report concludes with a section on policy implications, building on the presented analysis to suggest policy options that provide a pathway for the economic integration of the poor.